A free intercostal artery perforator flap as a salvage operation for a planned lumbar artery perforator flap with aberrant anatomy in breast reconstruction: A case report. Issue 5 (22nd January 2021) - Sharp, Olivia L.; Köhler, Guido; Masud, Dhalia; Haywood, Richard M.
Abstract: When autologous breast reconstruction is planned but abdominal tissue is not available, the lumbar artery perforator flap provides an alternative choice with minimal donor site morbidity. The lumbar and posterior intercostal arteries supply adjacent perforasomes on the posterolateral flank. The purpose of this report is to highlight the salvage of an autologous breast reconstruction free flap using a dorsal perforator of the posterior intercostal artery, when the planned lumbar artery perforators were not suitable. The patient was a 74‐year‐old with recurrent left‐sided breast cancer requiring immediate breast reconstruction. A lumbar perforator flap was planned as an oblique ellipse 19 × 10 cm. Intraoperatively, the two identified perforators traveled superiorly up to the 12th rib and therefore originated from the intercostal rather than lumbar arteries. The internal mammary artery and the vena comitants were used as recipient vessels, anastomosed to an interposition graft. Postoperatively, the patient was discharged home after 7 days without complication. Six months later, the patient was pleased with the reconstruction and had negligible donor site morbidity. The dorsal intercostal artery perforator flap therefore provides a salvage option when presumed lumbar artery perforators are dissected and found to be intercostal in origin.